A Eulerian-Lagrangian method for local scour incorporating a novel sediment initiation - Xuelian Guo; Steven N. Ward; Jiajia Wang; Lili Xiao; Wanshui Han (Ocean Engineering, 2026)

A method for long-distance traffic load reconstruction by fusing multi-source information - Pengtao Chen; Gan Yang; Mengfan Mao; Yang Jin; Shizhi Chen; Wanshui Han (Engineering Structures, 2025)

Experimental study of pressure distribution and wave forces on pile groups under extreme waves - Xi Yu; Jiajia Wang; Wanshui Han; Lili Xiao; Xin Xu; Kai Zhou; Silu Che; Xiaokun Chen; Mengqi Xia (Ocean Engineering, 2025)

Effects of pile groups and wave dynamics on the hydrodynamic load of offshore pile caps - Kai Zhou; Jiajia Wang; Wanshui Han; Lili Xiao; Xin Xu; Yuheng Xiang; Xi Yu (Ocean Engineering, 2025)

Experimental Study of Wave Load Distributions on Pile Groups Affected by Cap Structures and Pile Spacings Under Varied Wave Conditions - Wanshui Han; Kai Zhou; Jiajia Wang; Lili Xiao; Xin Xu; Yuheng Xiang; Xi Yu (Journal of Marine Science and Engineering, 2024)
Wave-induced forces pose significant challenges to marine structures, especially pile groups, where cap structures and pile spacings play critical roles in load distribution and structural stability. A physical wave flume experiment was conducted to investigate the influences of cap structures and pile spacings on wave load distributions under different wave conditions. Spatial and temporal variations in wave load distributions, including temporal variations in horizontal force, were measured as wave pressure rather than force. The results demonstrate that cap structures significantly alter the distributions of wave loads on pile groups. The integration of the cap increases the horizontal forces on the front pile and slightly reduces the vertical pressures across the pile group, particularly on the rear pile at relatively low elevations. The cap also delays the peak moment of horizontal force, especially in shallow water depths, where impact loads are more prominent and the cap induces water splash-back. Additionally, reducing pile spacing mitigates interference effects, optimizing the load distribution across piles by modulating flow velocity and pressure. The vertical pressure distribution exhibits a tiered pattern, with lower sections experiencing consistent loading, middle sections being subjected to higher loads at larger spacings, and upper sections being more affected by the cap at smaller spacings. As wave velocity and water depth increase, the differences in pressure intensity between pile groups with and without cap structures decrease, indicating the stabilizing effect of wave characteristics on structural response. This study provides insights into the design of marine pile group structures to optimize their performance characteristics under dynamic wave loading conditions.

Extreme Wave-Induced Pressure Distribution and Wave Forces on Tandem Pile Groups: An Experimental Study - Wanshui Han; Xi Yu; Jiajia Wang; Xin Xu; Xiaokun Chen (Journal of Marine Science and Engineering, 2024)
As the foundation of marine infrastructure, pile groups are subjected to extreme wave loads. Existing research primarily focuses on regular waves and wave forces. There is limited research on the pressure distribution of pile bodies under extreme waves. This paper describes a wave flume experiment where waves of a self-proposed extreme wave type were generated. The experiment considers three water depths (25/35/45 cm), three wave-pushing velocities (20/30/40 cm/s), and two clear distances (D, 2D). A total of 216 measuring points equipped with digital pressure sensors captured the vertical and circumferential pressure distribution and wave positive force. The results show that (1) the vertical and circumferential pressure distribution patterns of each component pile and the single pile are similar in various loading scenarios and clear distances. (2) The measuring point pressure, pressure after circumferential integration, and wave positive force are positively correlated with wave-pushing velocity. (3) The wave pressure is positively correlated with the water depth, while the pressure after circumferential integration is negatively correlated with the water depth. (4) When the clear distance is D, the wave positive force coefficient of each component pile is less than 1.0.

Experimental study of dynamic pressure and wave load on variform vertical cylinders under extreme waves - Xin Xu; Jiajia Wang; Wanshui Han; Lili Xiao; Zhiqiang Li; Hao Chen (Ocean Engineering, 2024)

Safety Assessment of Coastal Bridge Superstructures with Box Girders under Potential Landslide Tsunamis - Wanshui Han; Xin Xu; Jiajia Wang; Lili Xiao; Kai Zhou; Xuelian Guo (Journal of Marine Science and Engineering, 2023)
The superstructure of a coastal bridge is prone to overturn or unseating under a catastrophic tsunami, which seriously affects the post-disaster emergency rescue. In this paper, we establish a safety assessment framework for the superstructure of a bridge with a box girder under a potential landslide tsunami, and apply it to an in-service box girder and Baiyun Slide Complex on the southeast coast of China. First, a meshless numerical approach called Tsunami Squares (TS) is used to predict the movement of landslides and tsunamis. Additionally, we introduce the velocity-weakening basal friction effect in the model to optimize the landslide dynamics. Second, the maximum lateral and vertical wave loads on a box girder can be estimated using the time series of the wave height and velocity in the TS model. Third, we construct a safety evaluation method for the superstructure using the reaction of the bearing as the critical index. The results indicate that the framework developed here provides instructive guidance for evaluating the safety of coastal bridge superstructures during tsunami disasters, and we discuss the influence of the basal friction effect, bridge elevation, and support type on the structural safety.

A comparative study on the transient wind-induced response of long-span bridges subject to downbursts and typhoons - Yu Feng; Quanke Su; Jianming Hao; Wanshui Han; Haifeng Wang (Engineering Structures, 2023)